Types of Rhymes in Amal Donqol’sCrying in Front of Zarqaa el Yamama - Havazen Hossein Saleh (دراسات في اللغة العربيّة وآدابها)
Rhyme is a core element in the traditional poetry. The literary critics consider it a required condition for poetry. According to Qodamateb-ibn Jafar poetry should consist of metrical and rhymed language which conveys specific messages. However, rhyme, like other elements of poetry, has undergone changes to adapt to other contemporary changes in the area of poetry, so much so that it is referred to as New Poetry. The New Poetry approached rhyme in a new way, redefined it, removed the monotony of the ending of the poetry lines and changed its position from the end of the lines to the end of the poetic idea units. The structural difference between the traditional Ode and Modern Ode brought about different types and levels of rhyme. Today, poets do not insist on the use of rhyme I their poems; they use it only if it perform a function particularly to convey some meaning. Rhymes no longer enjoy unvaried forms in the odes; poets change them to suit their inner feelings.